PEOPLE WITH DISABILITIES IN UZBEKISTAN ARE UNDER THE PROTECTION OF THE LAW - Hayitova Farida Kuchkarovna (Journal Park Publishing, 2023)
The article talks about the work being done for the education of children with disabilities, inclusive education and the adopted law on this education, as well as the current problems and shortcomings in this regard.
Keywords: disability, persons with disabilities, inclusive education, law, Constitution of the Republic of Uzbekistan, Universal Declaration of Human Rights, Article, UN, Convention, inclusive life, NGO.